Modeling of ballistic-failure mechanisms in gas metal arc welds of mil a46100 armor-grade steel. Issue 3 (5th May 2015) - Grujicic, Mica; Ramaswami, Subrahmanian; Snipes, Jennifer; Galgalikar, Rohan; Yavari, Ramin; Yen, Chian-Fong; Cheeseman, Bryan; Montgomery, Jonathan
Abstract : Purpose: – The purpose of this paper is to discuss the recently developed multi-physics computational model for the conventional Gas Metal Arc Welding (GMAW) joining process that has been upgraded with respect to its predictive capabilities regarding the spatial distribution of the mechanical properties controlling the ballistic limit (i.e. penetration resistance) of the weld. Design/methodology/approach: – The original model consists of five modules, each dedicated to handling a specific aspect of the GMAW process, i.e.: electro-dynamics of the welding-gun; radiation-/convection-controlled heat transfer from the electric arc to the workpiece and mass transfer from the filler-metal consumable electrode to the weld; prediction of the temporal evolution and the spatial distribution of thermal and mechanical fields within the weld region during the GMAW joining process; the resulting temporal evolution and spatial distribution of the material microstructure throughout the weld region; and spatial distribution of the as-welded material mechanical properties. The model is upgraded through the introduction of the sixth module in the present work in recognition of the fact that in thick steel GMAW weldments, the overall ballistic performance of the armor may become controlled by the (often inferior) ballistic limits of its weld (fusion and heat-affected) zones. Findings: – The upgraded GMAW process model is next applied to the case of butt-welding of MIL A46100 (a prototypical high-hardness armor-grade martensitic steel) workpieces using filler-metal electrodes made of the same material. The predictions of the upgraded GMAW process model pertaining to the spatial distribution of the material microstructure and ballistic-limit-controlling mechanical properties within the MIL A46100 butt-weld are found to be consistent with general expectations and prior observations. Originality/value: – To the authors' knowledge, the present work is the first reported attempt to establish, using computational modeling, functional relationships between the GMAW process parameters and the mechanical properties controlling the ballistic limit of the resulting weld.